Effects of light emitting diodes - led on regeneration ability of Coffea canephora mediated via somatic embryogenesis - Mai, Nguyen Thi; Binh, Phan Thanh; Gam, Do Thi; Khoi, Phan Hong; Hung, Nguyen Khac; Ngoc, Pham Bich; Ha, Chu Hoang; Thanh Binh, Ha Thi (Academia Journal of Biology, 2016)
Coffea canephora is one of the most important industrial plants in Viet Nam. However, over culturing and exploitation have caused the decline of coffee's yeild and commercial benefits. Light Emitting Diodes-LED has been widely applied in micropropagation with various advantages, such as highly efficiency, easily design and low cost. This paper aims to evaluate the applied ability of LEDs light on in vitro regeneration of high yield Coffea Canephora TR11. After 6 months, leaves explants cultured under both LEDs light and flourescent light induced callus cluster. Nevertheless, explants cultured under LED 4 (41%R: 21%B: 38%W) condition showed the highest percentage of embryogenesis-like callus, which accounted for approximately 81.48%. LED lights not only enhanced the germination percentage of C. canephora somatic embryos, but also shortened the germination times. It was accounted for about 95% of somatic embryos germinated after 20 days cultured under LED 2 (58%R: 21%B: 21%W), in comparision, only 83.22% of embryos developed after 30 days cultured under control light. On the other hand, LED lights seemed to inhibited the mature ability of coffe seedlings. However, the green-house training results showed that LED lights-origined plantlets still adapted and developed as well as those cultured under flourescent condition. This preminary results revealed the application ability of LED lights on in vitro micropropagation of coffee plants, esspecially C. canephora TR11 specie.